Silicon and the State : French innovation policy in the Internet age - Trumbull, Gunnar (Brookings Institution Press, 2004)
"In the early 1990s, French officials viewed with some concern the emerging and innovative high-technology sectors of the U.S. and British marketplace. Fearful of falling too far behind, the French government implemented a vast array of policies - from tax incentives for investing in risky high-tech start-ups to new standards for electronic signatures - designed to promote the commercialization of new economy technologies in France. The efforts have turned French innovation policy on its head. Traditional government and bank-financed research and development were replaced by private venture capital